The Effects of Demographic, Training, and Specialization Differences of Physicians in COVID-19 Treatment in Turkey. Issue 1 (30th September 2023) - Özbilen, Muhammet; Bostan, Sedat; Kaya, Ahmet; Kaya, Yasemin; Kurt, Celali
Abstract : Introduction: The study aimed to determine how physicians' professional and institutional characteristics affect their treatment approaches for COVID-19 antiviral and supportive treatment, as well as their demographic characteristics and participation in COVID-19 trainings that may influence these orientations. Methods: After researching the literature and conducting interviews with the experts, a questionnaire was prepared. The convenience sampling method was used to distribute the questionnaire online to 408 physicians across the nation in January 2021. Exploratory factor analysis was used to verify the research scale, and the Cronbach's Alpha test was used to confirm its reliability. During the data analysis, descriptive and inferential statistical tests were used. Results: It was observed that the physicians were willing to give COVID-19 patients the antivirals but hesitant to provide and suggest supportive care. The training status for COVID-19 treatment was varied. Female physicians prescribed more antiviral drugs than male physicians, received more training, and scored higher across the scale than male physicians ( p = 0.001). The treatment approaches of physicians varied according to their specializations ( p = 0.002) all over the scale. Conclusion: The publication of current Ministry of Health guidelines on a variety of themes related to COVID-19 treatment, as seen in Turkey, is both beneficial and important. However, because all physicians, regardless of specialty, are affected by current and will be in the future pandemics, it is necessary to design and maintain a continuous training program on pandemics and their management for all physicians.